2006
DOI: 10.1111/j.1740-8709.2006.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

The education of health practitioners supporting breastfeeding women: time for critical reflection

Abstract: The protection, promotion and support of breastfeeding has now become a major international priority as emphasized in the Global Strategy for Infant and Young Child Feeding. Health practitioners, such as midwives, nurses and doctors, have a key role to play in providing support to breastfeeding women. This paper provides a critical discussion of educational requirements of health practitioners to equip them for their supportive role. The effective integration of embodied, vicarious, practice-based and theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 85 publications
(157 reference statements)
3
97
0
2
Order By: Relevance
“…It is difficult to quantify these because there is currently a lack of research relating specifically to the existing attitudes of new student midwives at the beginning of an infant feeding education programme. However, Dykes (2006) has identified that, among qualified midwives, personal and vicarious experiences of breastfeeding might have more influence on attitudes to the subject than cognitive knowledge. As such, those who do not feel positive about breastfeeding education might not be keen to attend sessions (Smale et al, 2006) or might demonstrate 'resentment' when required to do so (Burt et al, 2006).…”
Section: Student Midwives and Infant Feeding Perceptionsmentioning
confidence: 99%
“…It is difficult to quantify these because there is currently a lack of research relating specifically to the existing attitudes of new student midwives at the beginning of an infant feeding education programme. However, Dykes (2006) has identified that, among qualified midwives, personal and vicarious experiences of breastfeeding might have more influence on attitudes to the subject than cognitive knowledge. As such, those who do not feel positive about breastfeeding education might not be keen to attend sessions (Smale et al, 2006) or might demonstrate 'resentment' when required to do so (Burt et al, 2006).…”
Section: Student Midwives and Infant Feeding Perceptionsmentioning
confidence: 99%
“…This finding was for practitioners actively working in their chosen health professions. While Dykes' paper [18] identified, and Brodribb [17] surveyed current courses in Australia, they both statethat there is no consistent multidisciplinary education model available. Renfrew's study [30] found that interactive networks and partnerships across disciplines and organisations were needed to enhance educational opportunities and staff development.…”
Section: Practicing Health Professionalsmentioning
confidence: 99%
“…These were biases that will need to be considered in future research. The majority of the works noted in this review have differentiated between male and female health practitioners, [9,15,18,19,34] which has highlighted both experiential and gender biases. However, further research is needed to clarify whether male medical practitioners feel less comfortable working with breastfeeding mothers than their female colleagues.…”
Section: North Americamentioning
confidence: 99%
See 2 more Smart Citations